Investigations on grid connected PV system under variable irradiation conditions - Sreenivasa Reddy, G; Bramhananda Reddy, T; Vijaya Kumar, M (International Journal of Engineering and Technology, 2018)
A solar photovoltaic panel or a solar PV module is a device, which is to be considered universality the basic constituent of a solar photovoltaic system and is a combination of series and parallel assembly of solar cells. The electrical performance of this solar photovoltaic module be contingent on different environmental situations like PV cells/module solar spectral (air mass), ambient temperature, solar irradiance, angle-of-incidence.With these dependent conditions, there will be a petite chance to operate at its maximum power point (MPP) Hence, a Perturb and Observe (P&O) MPP algorithm is employed which draws considerable power with the desired time response. In present work, the interfacing of Solar PV system with the utility grid system which is having 15kW based on the Voltage Oriented Control (VOC). The temperature of the individual photovoltaic cell and solar irradiation are to be considered as inputs for the simulation process, whereas the duty cycle of the DC-DC boost converter is an output of the P&O controller. Performance of this grid-connected PV system with VOC method is analyzed with the simulation results and %THD values of the voltage and current at coupling point is verified. The results show the superiority of VOC method and its high dynamic behavior under variable irradiation conditions.Â Â